Media coverage of the migrant crisis in Bosnia and Herzegovina: How the narative shapes the perception of mixed migration - Buzar, Mirsad; Bašić, Ilarija (Crisis Management Days, 2025)
The migrant crisis in Europe, which has been ongoing since 2015, has not passed by Bosnia and Herzegovina (BiH). It is estimated that between the beginning of 2018 and the beginning of 2025, more than 150,000 irregular migrants have passed through BiH on their way to European Union (EU) countries as their final destination. BiH has been faced with an increased influx of migrants or mixed migration flows, which has brought a variety of challenges and problems. The relevant institutions were not sufficiently prepared to respond to this crisis, and political actors imposed not only crisis communication, carried by the media, but also a sense of (de)stabilization and (in)security through a securitization approach. The question is whether the concept of securitization has prevailed in the media space, whether these issues have caused problems at the domestic level, and to what extent has it influenced the general perception of citizens about this phenomenon in Bosnia and Herzegovina? The aim of this paper is to analyze the statements of BiH political actors on mixed migration flows in BiH in the period from 01.07.2020 to 30.06.2021, the year in which the largest number of migrants resided in BiH, and the research included an analysis of 20 BiH media and their 1,065 publications.